Analysis of M-Banking Service Factors on Customer Satisfaction at Indonesian Sharia Banks Kc Mamuju - Puti Mandasari; Muzdalifah Muhammadun; Syahriyah Semaun; St Aminah; Andi Bahri S (Jurnal Ekonomi Balance, 2024)
Business competition in the banking sector is now increasingly fierce, both in domestic and international markets. The quality of customer service is the main key for banking companies to maintain customer trust and satisfaction. In providing optimal service, the bank integrates technology through Mobile Banking (m-banking) services to meet customer needs. This research aims to evaluate the influence of various aspects of m-banking, such as system security, company credibility, ease of use, and speed on customer satisfaction at Bank Syariah Indonesia KC Mamuju. Quantitative research methods were used by collecting data through questionnaires to 94 respondents. The research results show that the variables of system security, company credibility, and m-banking speed positively influence customer satisfaction, with a joint influence reaching 56.4%. Multiple linear regression analysis shows that system security (X1), company credibility (X3), and speed (X4) have a significant positive influence on customer satisfaction (Y). The resulting regression equation is Y = 2.624 + 0.227 X1 + 0.211 X3 + 0.407 X4 + e. Thus, it can be concluded that the higher the quality of m-banking services, the greater customer satisfaction at Bank Syariah Indonesia KC Mamuju will increase. However, there were 2% complaints, indicating that improvements are still needed to improve the m-banking user experience.